A short peptide hydrogel with high stiffness induced by 310-helices to beta-sheet transition in water - Hiew, Shu Hui (2020)
Biological gels generally require polymeric chains that produce long-lived phys- ical entanglements. Low molecular weight colloids offer an alternative to macro- molecular gels, but often require ad-hoc synthetic procedures. Here, a short biomimetic peptide composed of eight amino acid residues derived from squid sucker ring teeth proteins is demonstrated to form hydrogel in water without any cross-linking agent or chemical modification and exhibits a stiffness on par with the stiffest peptide hydrogels. Combining solution and solid-state NMR, circular dichroism, infrared spectroscopy, and X-ray scattering, the peptide is shown to form a supramolecular, semiflexible gel assembled from unusual right-handed 310-helices stabilized in solution by π–π stacking. During gelation, the 310-helices undergo conformational transition into antiparallel β-sheets with formation of new interpeptide hydrophobic interactions, and molecular dynamic simulations corroborate stabilization by cross β-sheet oligomeriza- tion. The current study broadens the range of secondary structures available to create supramolecular hydrogels, and introduces 310-helices as transient building blocks for gelation via a 310-to-β-sheet conformational transition.